HBR guide to building your business case - Sheen, Raymond (Harvard business review guides., 2022)
Get your idea off the ground. You've got a great idea that will increase revenue or boost productivity-but how do you get the buy-in you need to make it happen? By building a business case that clearly shows your idea's value. That's not always easy: Maybe you're not sure what kind of data your stakeholders will trust. Or perhaps you're intimidated by number crunching. The HBR Guide to Building Your Business Case, written by project management expert Raymond Sheen, gives you the guidance and tools you need to make a strong case. You'll learn how to: spell out the business need for your idea; align your case with strategic goals; build the right team to shape and test your idea; calculate the return on investment; analyze risks and opportunities; and present your case to stakeholders.